LEGAL BASIS FOR PREVENTION OF CONFLICTS OF INTEREST - Gadoev A.Y., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article explores and analyzes the meaning and nature of the conflict of interest, as well as the issues of its prevention.